Management of APB DESA in Community Empowerment in Sejegi Village, East Mempawah District, Mempawah Regency - Anwar, Hairil; Chainar, Chainar; Rasidar, Rasidar; Desca Thea Purnama; marini, marini (International Journal of Education, Vocational and Social Science, 2023)
The purpose of this study is to describe the Management of APBDesa (Village Fund Allocation) in Community Empowerment in Sejegi Village, East Mempawah District, Mempawah Regency. This type of description research uses qualitative methods and data collection techniques through observation, interviews and documentation. Informants are determined by purposive techniques, consisting of the Village Secretary, BPD Chairman, Kadus, and the people of Sejegi Village. Research analysis according to Miles and Huberman includes data reduction, data display, and verification/conclusion. The results of the study illustrate; That APBDesa (Village Fund Allocation) management is quite transparent, and the 2022 budget plan and realization have been published to the public. Accountability of the APBD Accountability Report is late, and LPJ is incompletely submitted by the Head of the District to BPD which has implications for the performance assessment of the Kades. Participation in the planning and implementation of APBDesa management has involved the community through MUSDUS (Dusun Meeting) and MUSDES (Village Meeting), and involvement in village development projects. The effectiveness in planning the APBDesa (Village Fund Allocation) has not been effective, the small budget allocated for the field of community empowerment, the field of development, and the field of community development, and the construction of Village Offices are not on target. The efficiency of ADD implementation has not been efficient, the field of village government administration has received a larger allocation than the field of empowerment and the occurrence of budget wastage. Community empowerment has not been optimal, due to low community awareness and leadership factors of the village head, lack of budget and programs, and the absence of Village BUM as a village economic institution.